Analisis Pengaruh Profitabilitas Terhadap Harga Saham Yang Terdaftar Di Jakarta Islamic Index (JII) Periode 2012-2014 - Sukma Guruh, Pratama; , Dr. Daryono Soebagiyo, MEc; , Dr. Imron Rosyadi M.Ag (2015)
This research was conducted to examine the effect ratio of profitability such as NPM, ROA, ROE, EPS, DER, PBV and PER simultaneously or partially. The sample in this study is a company registered in the Jakarta Islamic Index (JII) in the period 2012 through 2014. Testing of this research was conducted using classic assumption test, which consists of normality test, multicollinearity, heteroscedasticity test, atutokorelasi. After that tested multiple linear regression were performed to determine the regression equation showing the relationship with the dependent variable specified independent variable. F test was conducted to determine whether the seven independent variables simultaneously affect the dependent variable. The t-test is used to see the significance of individual independent variable on the dependent variable to consider other variables constant. The results showed that together NPM, ROA, ROE, EPS, DER, PBV and PER have an effect on stock prices at JII. While individual variables that have an impact on stock prices in the JII is NPM, ROA.